Affecting commute mode choice in Southern California: Which employer-based strategies work? - Kane, Kevin; Hsu, Jenneille; Cryer, Joseph; Anderson, Marco (Journal of Transport and Land Use, 2020)
Interest in mandatory employer-based trip reduction (EBTR) programs has been renewed due to increased emphasis on reducing transportation-related greenhouse gas emissions. This paper analyzes survey data from 2004 to 2016 from an EBTR program in Southern California, known as Rule 2202, which allows employers with more than 250 workers to choose among implementing commute reduction strategies to meet performance standards, show evidence of obtaining omissions credits, or pay a fee-in-lieu. We report program statistics and conduct bivariate and regression analyses to determine which land-use and location characteristics, employer characteristics, and mitigation strategies explain cross-sectional differences in average vehicle ridership (AVR) and AVR improvement to understand where future AVR increases might be realized. Decreasing program participation suggests that alternatives to commute-reduction strategies make financial sense to regulated employers, but Rule 2202 employers report higher alternative transportation shares than the region as a whole. AVR is found to be highest at smaller worksites, in transit-supported and pedestrian-friendly neighborhoods, and where employers support vanpool programs. Multivariate analyses indicate that AVR gains were also highest in commercially dense neighborhoods, for retail businesses, and where guaranteed ride home programs were offered, showing promise for future AVR gains.